BUDAYA TELLASEN TOPAK: DARI KETUPAT KE IDE AKTIVITAS SPATIAL SKILLS DALAM PEMBELAJARAN MATEMATIKA - Ulfa, Sukriya; Wardhani, Indah Setyo; Syauqina, R. A. Qothrun Nada; Chusna, Noril Lailatul; Fijriyah, Izzah (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
Tellasen topak, which is identical to ketupat, is a culture of choosing, weaving, and processing janur into a medium for ketupat food. This culture is full of spatial skills activities, because it turns two-dimensional objects into space objects (three-dimensional). The purpose of this study is to explore the idea of spatial skills activities from ketupat in mathematics learning. The research method is qualitative research. Data collection techniques are observation, documentation, and internet search. Data analysis is in the form of data reduction, data presentation, and conclusion. The results concluded that in choosing, weaving, and processing janur into a medium for ketupat food, there are spatial skills activity ideas in the form of spatial visualization, spatial orientation and spatial rotation. In math learning, these ideas play a role in explaining the concepts of geometry, measurement and number. The results of this study contribute to mathematics learning, namely in developing culture-based teaching modules.